Banana Cultivars Microshoot Induction and Plantlet Formation Using Cytokinin and Auxin - Sugiyono Sugiyono; Prita Sari Dewi; Rendie Prasetyo (Universitas Sebelas Maret, 2021)
Banana is a horticultural plant with very high potentials, which contains carbohydrates and vitamins that are useful in fulfilling people's food and nutritional needs. Hence, this study aims to produce superior banana seedlings and develop a protocol for their mass production using a plant in vitro culture technique. This was a two stage-experiment i.e. microshoot production and plantlet formation. The result showed that Gebyar cultivar produced more shoots than the Kepok Kuning cultivar, with an average of 4.25 microshoots explant-1. However, Kepok Kuning produced more leaves than Gebyar, with an average of 4.64 leaves plantlet-1. Banana shoots cultured on the media containing Indole-3-acetic acid (IAA) at a concentration of 2.5 µM produced the highest leaves number. Meanwhile, those cultured on the media containing 1-Naphthalenesacetic acid (NAA) at a concentration of 7.5 µM produced the highest roots number. A Murashige and Skoog (MS) medium supplemented with 6-Benzylaminopurine (BAP) up to 30 µM and the one supplemented with 7.5 μM of NAA are suitable for Kepok Kuning and Gebyar cultivars micropropagation with regard to microshoot induction and plantlet formation, respectively.